(untitled) (Historia, 2021)
English Land rights in South Africa : a 19th century Transvaal perspective When analysing the settlement of whites in the Transvaal during the 19th century, it becomes clear that at least in some instances whites were infringing on traditional African land. Although African reserves were demarcated in the 19th century, the land allocated for this purpose was limited and not all African groups were involved. Because of various considerations it would however be difficult for the present South African Government to use this information as the predominant basis for a possible policy of land restitution before 1913. Afrikaans ’n Ontleding van blanke vestiging in Transvaal in die 19de eeu, toon duidelik aan dat daar ten minste in sommige gevalle inbreuk op tradisionele swart grond gemaak is. Hoewel daar reservate vir swart groepe in die 19de eeu afgebaken is, is slegs beperkte grondgebied daarvoor aangewend en was nie alle swart groepe daarby betrokke nie. Vanweë verskillende oorwegings sou dit egter vir die huidige Suid-Afrikaanse regering moeilik wees om ’n moontlike beleid vir die herstel van grondregte voor 1913 regstreeks op sulke inligting te baseer.